2016
DOI: 10.1108/jepp-03-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Indirectly productive entrepreneurship

Abstract: Purpose – Since Baumol (1990), the economic literature has distinguished between two broad categories of entrepreneurship: productive and unproductive. The purpose of this paper is to introduce another subcategory: indirectly productive entrepreneurship. Sometimes, profit-seeking entrepreneurs allocate their talents to indirectly productive activities to mitigate the new costs market participants endure as a result of a government regulation. The resources used to mitigate these costs must be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is also worth recognizing that the entrepreneurship as a concept has been evolving over years and that its conceptualization has also been changing. For example, in the middle ages, entrepreneurship was used to refer to an individual's ability to manage large production projects (Padilla and Cachanosky, 2016). This way, the focus was on the individual's ability to manage the projects using the available resources but not on the ability of individual to take risks.…”
Section: Definition Of Entrepreneurshipmentioning
confidence: 99%
“…It is also worth recognizing that the entrepreneurship as a concept has been evolving over years and that its conceptualization has also been changing. For example, in the middle ages, entrepreneurship was used to refer to an individual's ability to manage large production projects (Padilla and Cachanosky, 2016). This way, the focus was on the individual's ability to manage the projects using the available resources but not on the ability of individual to take risks.…”
Section: Definition Of Entrepreneurshipmentioning
confidence: 99%
“…As such, given that this option is sometimes not available to most new and small businesses, they resort to approaches that alter the institutions through their market activities (Elert, Henrekson, & Stenkula, 2017). Prior studies (e.g., Padilla & Cachanosky, 2016;Lawrence & Suddaby 2006) suggest that survival amidst institutional voids necessitates an adequate level of learning in order to create innovative initiatives to exploit the opportunities from institutional gaps and alleviate the negative influence of institutional inefficiencies. This is especially because advice seeking is vital for understanding what is actually happening in the environment in order to take advantage of the type of institutional void present and identify business opportunities that will lead to the creation of a new business venture and or further enhance their current business offering.…”
Section: Institutional Theory and Institutional Voidsmentioning
confidence: 99%
“…Future research can focus on the importance of different types of networking in different stages of business emergence. Fifth, a few recent research have revealed that some entrepreneurs perceive institutional gaps or voids as profit opportunities to be exploited (Padilla and Cachanosky, 2016;Smallbone and Welter, 2012). Such entrepreneurs, through their entrepreneurial initiatives, sometimes change the whole institutional structure in which they are located.…”
Section: Jeee 113mentioning
confidence: 99%